2015
DOI: 10.1107/s2056989015011354
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of deuterated sodium molybdate dihydrate and sodium tungstate dihydrate from time-of-flight neutron powder diffraction

Abstract: High-precision structural parameters for Na2MoO4·2D2O and Na2WO4·2D2O are reported based on refinement of high-resolution time-of-flight neutron powder diffraction data. Complementary Raman spectra are also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
(39 reference statements)
0
2
0
Order By: Relevance
“… Note. ν exp /cm −1 , ν cal /cm −1 , and ν ref /cm −1 refer to the room temperature Raman bands experimentally observed, calculated using CASTEP, and reported in the literature, respectively, for NWHO crystal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Note. ν exp /cm −1 , ν cal /cm −1 , and ν ref /cm −1 refer to the room temperature Raman bands experimentally observed, calculated using CASTEP, and reported in the literature, respectively, for NWHO crystal.…”
Section: Resultsmentioning
confidence: 99%
“…Busey et al pointed out an asymmetric stretching vibrational mode of H 2 O in the NWHO Raman spectrum (~3,300 cm −1 ) and two bending vibrational modes in its infrared spectrum (1,680 and 1,695 cm −1 ). Having studied Raman spectrum of NWHO, Fortes observed the bending vibrational mode of H 2 O at 1,683 cm −1 and considered that the envelope corresponding to stretching vibrational mode of H 2 O approximately at 3,300 cm −1 can be divided into four peaks (3,100, 3,297, 3,358, and 3,455 cm −1 ). Saraiva et al recorded Raman spectra of polycrystalline NWHO at low temperatures between 13 and 295 K and found that the envelope of H 2 O in the region between 3,175 and 3,450 cm −1 splits as temperature decreases, indicating the evidence of the conformational changes of the crystal.…”
Section: Introductionmentioning
confidence: 99%